The Legacy of Joseph A. Moylan, M.D.: "It's About Everyone Else". Issue 1 (1st March 2021) - Mosca, Paul J.; Zani, Sabino; Haglund, Michael M.; Collins, Bradley H.; Wasiolek, Sue; Pappas, Theodore N.; Kirk, Allan D.; Cendales, Linda C.
Abstract : The history of modern American surgery is marked by larger-than-life pioneers who have made transformative contributions to our field. These extraordinary individuals have been known primarily for their technical and clinical mastery, development of novel surgical procedures and techniques, extraordinary abilities in the education and training of surgeons, and/or innovative discoveries in biomedical science. While mastery in clinical surgery, education, and research have come to characterize the consummate academic surgeon, challenging social inequities of today now demand deeper engagement in another vital arena. This historical account is the story of a truly exceptional surgeon and visionary who spent much of his life leading that very charge. Early in his career, Dr. Joseph Moylan recognized and embraced this obligation to go beyond the walls of the hospital and out into the community to combat social factors leading to adverse outcomes for at-risk young men. His legacy itself represents a vehicle for empowering youth confronted with barriers to educational opportunities and experiences. Furthermore, recounting Joe's journey conveys the over-arching thesis that surgeons have the opportunity—and, indeed, are well positioned—to engage more deeply with their communities, to lead efforts to address social determinants at their roots and to create a pipeline of bright young scholars and potential future surgeons. Abstract : Mini Abstarct: Joseph A. Moylan, MD, was a consummate academic surgeon and leader who made an indelible imprint on those he served and those who knew him. At the heart of his legacy, though, was the school he founded to lift up, empower, and prepare at-risk youth for a successful future, as well as the community's enduring commitment to his cause.